2022
DOI: 10.1136/gutjnl-2021-325632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lumen-apposing metal stents versus double-pigtail plastic stents for infected necrotising pancreatitis

Abstract: ObjectiveLumen-apposing metal stents (LAMS) are believed to clinically improve endoscopic transluminal drainage of infected necrosis when compared with double-pigtail plastic stents. However, comparative data from prospective studies are very limited.DesignPatients with infected necrotising pancreatitis, who underwent an endoscopic step-up approach with LAMS within a multicentre prospective cohort study were compared with the data of 51 patients in the randomised TENSION trial who had been assigned to the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 29 publications
0
45
0
1
Order By: Relevance
“…We read with great interest the study published by Boxhoorn et al , comparing lumen-apposing metal stents (LAMS) versus double-pigtail plastic stents (DPPS) for treatment of infected necrotising pancreatitis 1. The authors did not find a significant difference in the primary aim, that is, the need for endoscopic transluminal necrosectomy, based on an indirect comparison between a multicentre prospective cohort treated with LAMS (step-up approach) and a previous cohort from the TENSION randomised controlled trial (RCT), where patients were treated with DPPS according to a similar protocol 2…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the study published by Boxhoorn et al , comparing lumen-apposing metal stents (LAMS) versus double-pigtail plastic stents (DPPS) for treatment of infected necrotising pancreatitis 1. The authors did not find a significant difference in the primary aim, that is, the need for endoscopic transluminal necrosectomy, based on an indirect comparison between a multicentre prospective cohort treated with LAMS (step-up approach) and a previous cohort from the TENSION randomised controlled trial (RCT), where patients were treated with DPPS according to a similar protocol 2…”
mentioning
confidence: 99%
“…When patients in a single study are treated by several therapists, there is good reason to suspect that variation in outcome will be smaller for patients treated in the same group than for patients treated in different groups. This potential correlation of outcomes results in a loss of independence of observations, in particular when the number of patients enrolled per centre is different, as could have occurred in the study by Boxhoorn et al 1. As a consequence, reporting this information and accounting for clustering through several statistical methods, such as randomising patients within each cluster, would represent a strength in these multicentre studies 5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the endoscopic operation time was shorter in patients with LAMS despite the higher incidence of complications and costs. In contrast, another prospective cohort study enrolled 53 patients with IPN and found that the number of endoscopic transluminal necrosectomy procedures, incidence of complications, and total healthcare costs were comparable between the two stents 33 . The results of two ongoing randomized controlled studies will further evaluate the clinical e cacy and possible complications 34,35 ; however, shorter endoscope operation times with LAMS are unambiguously evident, which is a potentially crucial advantage for more critical cases 12,32 .…”
Section: Discussionmentioning
confidence: 96%
“…Patients with LAMS had a higher clinical success rate, shorter procedure time, and a lower probability of requiring surgery and recurrence than those with plastic stents. However, two recent prospective studies evaluating the clinical effects and associated complications of LAMS have shown mixed results 32,33 . In a randomized controlled trial by Bang et al involving 60 patients with pancreatitis and walled-off necrosis, patients with LAMS had similar technical success, treatment success, and the total number of procedures performed during the 6 months of follow-up was comparable to that obtained following placement of plastic stents 32 .…”
Section: Discussionmentioning
confidence: 99%